Quality of service and passenger perception of the taxi service in Changlun - Lee, Kuo Hsing; Razalli, Mohd Rizal (2012)
The purpose of the research is to measure the service quality of the taxi service in Changlun. In order to have a good grasp of grasp of passenger’s perception of taxi service quality of Changlun in Kedah, a proper method used to reflect passenger’s opinion accurately.A questionnaire survey conducted to know their opinion about the taxi service quality in Changlun. The quality service of the public transportation in Malaysia is lower compare to other developed country .This study aims to improve the public transportation service and improve passenger’s satisfaction to the taxi service in Malaysia.